Supplier evaluation for resilient project driven supply chain. (March 2019) - Shishodia, Anjali; Verma, Priyanka; Dixit, Vijaya
Highlights: Research focuses on evaluating supplier resilience of project-driven supply chain. Fuzzy based aggregation method used for quantifying supplier resilience attributes. Computed resilience scores aid in categorizing existing suppliers in groups. Activity wise analysis provides early warning signals for future preparedness. Suppliers segregation based on supplies feeding critical and non-critical activity. Abstract: Project-based organizations are increasingly becoming dependent on suppliers because of an upward trend of subcontracting and an emphasis on core competencies. Projects can be viewed as complex networks consisting of several interdependent actors, and among them, suppliers are important entities. In project-based firms, the demand of the material supply chain is driven by the material requirement of the project, which is referred to as project-driven supply chains (PDSCs). PDSCs couple off-site supply chain activities (i.e., production, logistics, and inventory) with on-site project activities (i.e., scheduling, resource planning, and allocation), and thus exposure of this integration to any disruption may impede the progress of the project. This study evaluates the resilience capacity of existing suppliers of PDSC. More precisely, the objectives of the study are to determine the factors influencing supplier's resilience in the context of PDSCs and to compute suppliers' resilience scores. The factors are identified using published literature and scores are computed using fuzzy linguistic guided order weighted aggregation (FLQ-OWA) technique. The proposed methodology is implemented in a real project case (construction of hospital/health care facility). The computed resilience scores enable activity-wise analysis of supplier's resilience which in turn, helps in classifying existing suppliers in distinct groups characterized by their resilience capability and providing early warning signals to the top managers of contractor's organization to work proactively with all corrective measures planned at the onset of the project.